The Effectiveness of Telegram Quizzes in Enhancing Arabic Language Content Mastery Among Participants of the Sabilurrasyad Arabic Course in Bandung: Efektivitas Kuis Telegram dalam Meningkatkan Penguasaan Materi Bahasa Arab bagi Peserta Kursus Bahasa Arab di Sabilurrasyad Bandung - Natasya Farhati Yunis (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2025)
Purpose – This study aims to investigate the implementation, effectiveness, strengths, and limitations of the Telegram quiz feature as a learning medium in Arabic language instruction. The study adopts a quantitative descriptive approach with an experimental research design. Design/methods/approach – The study employed a descriptive quantitative approach with an experimental design using a one-group pretest-posttest model. Data were collected through questionnaires and tests (pre-test and post-test) administered to 10 course participants. The results were then analyzed through hypothesis testing using a paired sample t-test. Findings – The findings indicate a significant difference in participants' mastery of Arabic language material after using the Telegram quiz. Based on data analysis from 10 course participants, a significant improvement in Arabic language mastery was observed following the use of Telegram quizzes, with mean scores rising from 89.90 (pre-test) to 94.60 (post-test) (Sig. = 0.027 < 0.05; t = 2.645 > tₜₐbₗₑ = 2.262). The Telegram quiz feature was found to be practical and user-friendly, offering a multiple-choice format that facilitates recall and comprehension of learning material. Its interface is engaging and enjoyable, and it provides immediate feedback on whether the selected answer is correct or incorrect. However, certain limitations were identified, including the small font size that can hinder readability, the inability of quiz creators to edit questions or answers once published, and the requirement for stable internet access or data availability for implementation. Research implications/limitations – These findings suggest that Telegram quizzes can serve as an effective alternative instructional medium for non-formal Arabic language education. However, the study is limited by its focus on a single social media platform and a small sample size. Originality/value – This study contributes to the expanding body of research on digital learning media by specifically addressing the pedagogical value of Telegram’s quiz feature, a tool that has received limited attention in the context of non-formal Arabic language instruction. Abstrak Tujuan – Penelitian ini bertujuan untuk mengkaji implementasi, efektivitas, kelebihan, dan keterbatasan fitur kuis Telegram sebagai media pembelajaran dalam pengajaran bahasa Arab. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan desain penelitian eksperimen. Desain/metode/pendekatan – Penelitian ini menerapkan pendekatan kuantitatif deskriptif dengan desain eksperimen menggunakan model one-group pretest-posttest. Pengumpulan data dilakukan melalui kuesioner dan tes (pre-test dan post-test) yang diberikan kepada 10 peserta kursus. Data hasil penelitian dianalisis menggunakan uji hipotesis dengan teknik paired sample t-test. Temuan – Hasil penelitian menunjukkan adanya perbedaan yang signifikan dalam penguasaan materi bahasa Arab peserta setelah menggunakan kuis Telegram. Berdasarkan analisis data dari 10 peserta kursus, terjadi peningkatan signifikan dalam penguasaan bahasa Arab setelah penggunaan kuis Telegram, dengan rata-rata skor meningkat dari 89,90 (pre-test) menjadi 94,60 (post-test) (Sig. = 0,027 < 0,05; t = 2,645 > tₜₐbₗₑ = 2,262). Fitur kuis Telegram dinilai praktis dan mudah digunakan, dengan format pilihan ganda yang memudahkan peserta dalam mengingat dan memahami materi pembelajaran. Antarmukanya menarik dan menyenangkan serta memberikan umpan balik langsung mengenai jawaban yang benar atau salah. Namun, terdapat beberapa keterbatasan, seperti ukuran huruf yang kecil sehingga mengganggu keterbacaan, tidak adanya opsi untuk mengedit soal atau jawaban setelah dipublikasikan, serta kebutuhan akan koneksi internet yang stabil atau ketersediaan data. Implikasi/batasan penelitian  – Temuan ini menunjukkan bahwa kuis Telegram dapat menjadi alternatif media pembelajaran yang efektif dalam pendidikan bahasa Arab non-formal. Namun, penelitian ini memiliki keterbatasan karena hanya berfokus pada satu platform media sosial dan jumlah sampel yang kecil. Orisinalitas/nilai – Penelitian ini memberikan kontribusi pada pengembangan kajian media pembelajaran digital dengan secara khusus menyoroti nilai pedagogis dari fitur kuis Telegram, sebuah alat yang masih jarang dibahas dalam konteks pengajaran bahasa Arab non-formal.